Effect of three production systems of central Mexico on growth performance of five lamb genotypes - J. R. Galaviz-Rodríguez; J. E. Ramírez-Bribiesca; S. Vargas-López; J. L. Zaragoza-Ramírez; J. D. Guerrero-Rodríguez; M. Mellado-Bosque; R. G. Ramírez (Journal of Animal and Plant Sciences, 2014)
A year study was undertaken to evaluate the effects of three contrasting management systems: year-round grazing (G), G plus cereal crop residues and grain supplementation (GS) and year-round pen feeding (PF) on performance of five genotypes of lambs in central Mexico. The variables type of birth (single/twin), sex (male/female), time of birth (dry/wet) and season of birth (autumn, winter, spring, summer) were studied. Genotype (5 breed groups) on birth weight (BW), weaning weight (WW), final weight (182 days of age; PW) and pre and post-weaning daily weight gains (DWG) were also studied. Live weight of the variable response showed a significant effect of breeds (P<0.0001), season (P=0.0031), type of birth (P=0.0005), and interaction in the production system x time x type of birth in the year (P=0.0038). There was also interaction in the production system x time x type of birth (P=0.0425). The overall weights (means ± standard error) for BW, WW, and PW were 4.8 ± 1.7, 20.6 ± 5.0 and 28.9 ± 7.0 kg, respectively. Means DWG were 187, 100 and 135 kg for pre-weaning, post-weaning and total weight, respectively. In general, wool lambs had better performance than hair lambs Thus, sheep production system in the high plateau of central Mexico have an important effect of lamb performance.
Keywords: Lamb production; Environmental factors; Birth weight; Weaning weight